Periodontal ligament and gingival fibroblasts participate in the production of TGF-β, interleukin (IL)-8 and IL-10 - Ana Carolina de Faria Morandini; Carla Renata Sipert; Erivan Schnaider Ramos-Junior; Daniel Thomas Brozoski; Carlos Ferreira Santos (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The aim of this study was to quantify and compare the production of transforming growth factor beta (TGF-β), interleukin (IL)-8 and IL-10 by human cultured periodontal ligament and gingival fibroblasts both obtained from the same donors challenged with lipopolysaccharide (LPS) from Porphyromonas gingivalis. Fibroblasts were exposed to 0.1-10 µg/mL of LPS from P. gingivalis and after 24 h the supernatants were collected and analyzed by enzyme-linked immunosorbent assay (ELISA). TGF-β protein production was upregulated in a concentration-dependent manner, mainly in gingival fibroblasts, which was statistically significant when challenged by 10 µg/mL LPS. Additionally, at this concentration, gingival fibroblasts had almost a two-fold increase in the amount of TGF-β when compared to periodontal ligament fibroblasts. Both periodontal ligament and gingival fibroblasts showed an increase in IL-8 production when challenged with 1 µg/mL and 10 µg/mL LPS. IL-10 production remained unaffected when challenged by any of the LPS concentrations tested in either periodontal ligament or gingival fibroblasts. Our results demonstrate that periodontal ligament and gingival fibroblasts when challenged by LPS from P. gingivalis with 24 h may play a critical role in producing TGF-β and IL-8 but not IL-10.